Kajian Dinamika Faktor Sosio-Ekonomi dan Kriminalitas untuk Penguatan Pertumbuhan Ekonomi Indonesia - Wahyuningrum, Dinar; Faridatussalam, Sitti Retno; Ambarsari, Rosa (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
era of rapid advancements in science, technology, and cultural dynamics, significant shifts have occurred in various aspects of human life, such as ideology, society, economy, arts, and morals. These changes have influenced the values within society, with materialism and hedonism becoming more prevalent. While such value changes can bring positive outcomes, they also lead to negative behaviors, including criminal actions. The increasing criminal activity in Indonesia has become a serious concern, with high crime rates that demand attention from both the government and law enforcement agencies. This study aims to analyze the relationship between crime and economic conditions across 34 provinces in Indonesia, focusing on the impact of economic components such as consumption patterns, unemployment, the quality of human resources (measured through education), and population density on crime rates in Indonesia from 2018 to 2022. The findings of the study indicate that unemployment, low human resource quality reflected in education levels, and population density are significant factors influencing crime rates in Indonesia. Economically, unemployment and poor educational quality are the primary drivers of criminal behavior. Additionally, high population density exacerbates the situation, as densely populated areas tend to experience social tension and conflicts that can trigger criminal acts. Therefore, to reduce crime rates, coordinated efforts are required, including improving educational quality, providing more job opportunities, managing population density, and enhancing the economic well-being of society. This study highlights the importance of government and related institutions in creating policies to address the economic factors contributing to crime, in order to build a safer and more prosperous society.